Implementation of Discovery Learning Strategy in Improving Mathematics Cognitive Learning Outcomes in Grade V Students at SDN Alasrajah 2 Blega - Mauidatul Hasanah; Muhammad Sahrul Mubarok (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
This study aims to improve students' cognitive learning outcomes in Mathematics, particularly on the topic of fraction addition, through the implementation of the Discovery Learning model. The background of this research is the low student learning outcomes caused by monotonous teaching methods that do not actively involve students in the learning process. This is a Classroom Action Research (CAR) conducted at SDN Alasrajah 2 Blega with 25 fifth-grade students as research subjects. The research was carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through observation, interviews, documentation, and tests (pre-test and post-test). The research instruments included teacher and student activity observation sheets, and learning outcome test items. The data were analyzed using descriptive quantitative analysis to observe the improvement in students' learning outcomes across cycles. The results showed a significant improvement in students’ cognitive learning outcomes. In the pre-action stage, the completeness level was 0% with an average score of 36.4. After the first cycle, the completeness increased to 44% with an average score of 64. In the second cycle, completeness reached 92% with an average score of 79.2. The study concludes that the Discovery Learning model is effective in enhancing students' understanding and performance in fraction addition. It is recommended that teachers apply this model as an alternative strategy in teaching Mathematics at the elementary level.